2021
DOI: 10.3390/nu13092977
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Vitamin B6 with All-Cause and Cause-Specific Mortality in a Prospective Study

Donghui Yang,
Yan Liu,
Yafeng Wang
et al.

Abstract: There is little evidence regarding the association between serum vitamin B6 concentration and subsequent mortality. We aimed to evaluate the association of serum vitamin B6 concentration with all-cause, cardiovascular disease (CVD), and cancer mortality in the general population using data from the National Health and Nutrition Examination Survey (NHANES). Our study examined 12,190 adults participating in NHANES from 2005 to 2010 in the United States. The mortality status was linked to National Death Index (ND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…However, a study from Caerphilly showed that vitamin B6 levels were associated with non-cardiovascular disease mortality in men, but not with cardiovascular or cancer mortality ( 29 ). Another study conducted on the general population also observed a negative association between PLP and all-cause mortality, but found no association with cardiovascular or cancer mortality ( 24 ). These discrepancies may be due to the different study populations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, a study from Caerphilly showed that vitamin B6 levels were associated with non-cardiovascular disease mortality in men, but not with cardiovascular or cancer mortality ( 29 ). Another study conducted on the general population also observed a negative association between PLP and all-cause mortality, but found no association with cardiovascular or cancer mortality ( 24 ). These discrepancies may be due to the different study populations.…”
Section: Discussionmentioning
confidence: 98%
“…Based on reviewing relevant literature ( 17 , 24 ), we selected the following covariates in the model: age (<70, 70-80 or ≥80 years), sex (male or female), drink (yes or no), smoke (never or former or current), education (Less than high school, High school or equivalent, and College or above), race ethnicity (Hispanic, non-Hispanic white, non-Hispanic black, and Race-including multi-racial), physical activity (low, moderate, or vigorous), cholesterol (≥6.2 mmol/L or <6.2 mmol/L), and self-reported physician diagnosed cardiovascular disease (yes or no), cancer (yes or no), hypertension (yes or no) and type 2 diabetes (yes or no). Body mass index (BMI) was calculated as weight (kg) divided by height (meters squared).…”
Section: Methodsmentioning
confidence: 99%
“…There is little evidence regarding the association between serum vitamin B1, B3, B5, and B6 and mortality in either general population or dialysis patients. Some research suggested higher levels of vitamin B6 were associated with a lower risk for all‐cause mortality in the general population [14]. But meta‐analyses showed that supplement B‐complex or niacin did not reduce all‐cause mortality or CV mortality [15].…”
Section: Discussionmentioning
confidence: 99%
“…A summary of findings from seven studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ] examining the relationship between B6 status and all-cause mortality in the general population is presented in Table 3 . Among these seven studies, six [ 23 , 24 , 25 , 26 , 27 , 28 ] indicated a significant inverse association between B6 status and all-cause mortality.…”
Section: Epidemiological Studiesmentioning
confidence: 99%